All sails to the NDU wind? Review of European Military Culture and Security Governance. Soldiers, Scholars and National Defence Universities by Tamir Libel - Maskaliunaite Asta (Journal on Baltic Security, 2018)
Reviews European Military Culture and Security Governance. Soldiers, scholars and national defence universities by Tamir Libel.